Cellulose Nanocrystals: Particle Size Distribution and Dispersion in Polymer Composites - Leng, Tianyang (Université d'Ottawa / University of Ottawa, 2016)
This thesis describes the characterization of the particle size distribution of cellulose nanocrystals (CNC), the synthesis and characterization of fluorescent CNCs, and the development of a fluorescence microscopy method to probe the distribution of fluorescent CNCs in polymer composites. In this thesis, several methods are used to characterize the size of CNC particles. Size distribution measurements by single particle counting methods (Transmission electron microscopy, Atomic force microscopy) are compared to an ensemble method, Dynamic lighting scattering (DLS) and differences between the various methods will be discussed. The effect of sonication on the CNC size distributions measured by AFM and DLS is examined. Furthermore, a reliable and reproducible method for re-dispersing dry CNC powder will be explored in this chapter since CNC is often stored in a dry environment due to its stability. Rhodamine B isothiocyanate (RBITC) and 5-(4,6-dichlorotriazinyl) amino fluorescein (DTAF) were selected for labelling CNCs. These dyes have the advantage of being cheap and readily available and compatible with relatively simple synthetic chemistry. The photophysical properties of all dye labeled CNCs were studied in more detail than in previous studies. The focus is on understanding the most appropriate labeling efficiency to maximize the ability to detect individual CNCs while minimizing the amount of dye used to avoid modifying the CNC properties. The characterization methods include ensemble methods such as UV-Vis absorption and scattering measurements, fluorescence spectroscopy and single molecule methods such as Total internal reflection fluorescence microscopy (TIRFM), Atomic force microscopy (AFM) and correlated TIRFM/AFM measurements. All of these methods have their advantages and disadvantages. After characterization, the most suitable dye labeled CNC sample was selected for development of a fluorescence microscopy method to characterize CNC distribution in CNC/polymer composites. The dye labeled CNC has been incorporated into polyvinyl alcohol (PVA) films and studied by fluorescence microscopy. These experiments demonstrated that the level of CNC agglomeration varies significantly for different film preparation methods, indicating that fluorescence microscopy is a useful and easily accessible method for optimizing film preparation. The self-quenching of the dye in the film was also measured and discussed and is an important consideration for choice of the dye loading and CNC content in the films.
Keywords: Cellulose Nanocrystals; AFM